Retailing in Electronic Commerce: Travel and Tourism Services Online - Mustakim Mustakim (Universitas Muhammadiyah Enrekang, 2019)
This paper discusses the role of electronic commerce in the retailing of travel and tourism services through online platforms. The study aims to explain the concept of online travel retailing, the types of services provided, special service features, the benefits and limitations of online travel services, and the broader impact of electronic commerce on the travel industry. The paper uses a descriptive qualitative approach based on literature review and conceptual discussion drawn from relevant references on e-commerce and online travel services. The discussion shows that the Internet has become an important communication, marketing, and distribution channel that enables travelers to search information, compare prices, make reservations, and purchase travel services more efficiently. Online travel services also provide added value through fare comparison, direct marketing, travel alerts, loyalty programs, and intelligent-agent support. From the provider perspective, online systems improve operational efficiency, expand market reach, and reduce intermediary and processing costs. However, online travel services also face several limitations, including unequal Internet access, difficulties for inexperienced users, reliability and security concerns, and the limited ability of online systems to handle complex travel arrangements requiring personalized assistance. The paper concludes that electronic commerce has significantly transformed the travel and tourism retail sector by increasing accessibility, efficiency, and competitiveness, although conventional travel agents still remain relevant for specialized and complex services.